Vaginal Hyperplasia In A Bitch – A Case Report - Manjunath, S.P.; Kumar, V. Prasanna; Gowda, C.T. Chandre; Pavankumar, K.N.; Deepak , A.V. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Vaginal hyperplasia is a condition most often seen in young bitch during proestrus and estrus. It is protrusion of doughnut-shaped excessive mucosal folding of vaginal floor cranial to urethral tubercle which becomes swollen (Post et al., 1991). In some bitches, the entire vaginal mucosal wall may be involved (Rushmer, 1980). Canine vaginal hyperplasia involves only the mucosa, which differ it from the condition seen in cattle, goats and sheep (Franklin, 1986: Hudson, 1986:). A case of vaginal hyperplasia in a bitch and its treatment is discussed in the present article.